Biosystems Engineering: Biofactories for Food Production in the Century XXI - Guevara-Gonzalez, Ramon; Torres-Pacheco, Irineo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book presents new food production systems (for plants and animals) involving agrochemicals that increase in a controlled manner the bioactives content, under greenhouse conditions. Moreover, conception and design of new instrumentation for precision agriculture and aquiculture contributing in food production is also highlighted in this book.
Plant Biosystems: From conventional to new Food production systems -- Agriculture for nutraceuticals -- The Plant immune system and Food Production -- Mathematical modelling for Biosystems -- Plant Biotronics as tool for Food Production Biosystems.-Exploring aquaculture as Food Biosystem -- Prototypes for aquaculture-plant Biosystems -- b.3. Aquaculture Biotronics -- Perspectives of Biosystems as sustainable strategy for Food Production in century XXI -- Concluding Remarks.
Keywords: Chemistry; Biotechnology; Food science; Industrial engineering; Chemistry; Food Science; Industrial and Production Engineering; Biotechnology